Anti‐BDCA2 monoclonal antibody inhibits plasmacytoid dendritic cell activation through Fc‐dependent and Fc‐independent mechanisms. Issue 4 (11th March 2015) - Pellerin, Alex; Otero, Karel; Czerkowicz, Julie M; Kerns, Hannah M; Shapiro, Renée I; Ranger, Ann M; Otipoby, Kevin L; Taylor, Frederick R; Cameron, Thomas O; Viney, Joanne L; Rabah, Dania
Abstract Type I interferons (IFN‐I) are implicated in the pathogenesis of systemic lupus erythematosus (SLE). In SLE, immune complexes bind to the CD32a (FcγRIIa) receptor on the surface of plasmacytoid dendritic cells (pDCs) and stimulate the secretion of IFN‐I from pDCs. BDCA2 is a pDC‐specific receptor that, when engaged, inhibits the production of IFN‐I in human pDCs. BDCA2 engagement, therefore, represents an attractive therapeutic target for inhibiting pDC‐derived IFN‐I and may be an effective therapy for the treatment of SLE. In this study, we show that 24F4A, a humanized monoclonal antibody (mAb) against BDCA2, engages BDCA2 and leads to its internalization and the consequent inhibition of TLR‐induced IFN‐I by pDCs in vitro using blood from both healthy and SLE donors. These effects were confirmed in vivo using a single injection of 24F4A in cynomolgus monkeys. 24F4A also inhibited pDC activation by SLE‐associated immune complexes (IC). In addition to the inhibitory effect of 24F4A through engagement of BDCA2, the Fc region of 24F4A was critical for potent inhibition of IC‐induced IFN‐I production through internalization of CD32a. This study highlights the novel therapeutic potential of an effector‐competent anti‐BDCA2 mAb that demonstrates a dual mechanism to dampen pDC responses for enhanced clinical efficacy in SLE.